Research on the impact of audience behavior based on emotional orientation effect of public service advertising - Huo, Junyan; Cheng, Chao (Nurture, 2023)
Purpose: This study analyzes the changes in feelings, attitudes, and behaviors of the audience after watching the Public Service Advertisements (PSA) and better evaluates which emotions are more acceptable to the audience of the PSA. Design/Methodology/Approach: In this study, 217 audiences from Eastern and Western nations were chosen to witness the effects of several emotionally intense Public Services Advertisements and gather data to assess the shifts in opinion and behavioural influences. Findings: Based on the results of the study, it can be shown that many social groups exhibit favorable responses to Public Services Advertisements (PSA) in terms of emotional effect perception, namely in relation to fear, comedy, and compassion. These findings indicate a generally good trend across all levels of analysis. Differences in audience attitudes and behavioural changes brought on by various levels of perception of advertising impact emerge under the influence of background circumstances. Conclusion: The emotional orientation have a favorable impact on the attitude and conduct of the audience, serving as a source of motivation, induction, and guidance. Research Limitations/Implications: This paper analyzes audience cognitive and behavioral research from only the emotion-oriented effect, and the actual emotion is inextricably linked with emotions and psychology. Some of the parts that have not yet been covered will be further studied in the future when conditions permit. Practical Implications: It can help trigger the audience’s emotional cognition, form long-term attention to public welfare information, and improve the possibility of changing the behavior of the public. Contribution to Literature: This study provides a research framework for the impact of the PSA effect on audience behavior and paves the way for later emotional effect research and design strategies.